2015
DOI: 10.1038/sc.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spinal cord injury in Tianjin, China: a single-center report of 354 cases

Abstract: were reviewed. Collected variables included gender, age, marital status, ethnic group, occupation, etiology, neurological level of injury, American Spinal Injury Association (ASIA)-ISCoS impairment scale at admission, the severity, death and its cause, concomitant injuries and treatment choice. Results: During the study period, 354 cases were identified. Male-to-female ratio was 2.34:1, with a mean age of 50.1 ± 15.5 years. Falls (55.1%), comprising low falls and high falls (33.6% and 21.5%, respectively), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
5
23
1
Order By: Relevance
“…Studies have showed that surgery is the main treatment especially for complete injuries because it can prevent further injuries and improve spinal cord conditions ( 17 , 19 , 23 , 25 27 , 33 ). But weather perform surgery was depend on the severity and extent of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that surgery is the main treatment especially for complete injuries because it can prevent further injuries and improve spinal cord conditions ( 17 , 19 , 23 , 25 27 , 33 ). But weather perform surgery was depend on the severity and extent of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] High-energy injuries often occur in young people, in addition to the spinal injury, more along with the corresponding segment of spinal cord injury and other organs injury. [4][5][6][7] Low-energy injuries, often occur among the elderly population due to etiologies such as osteoporosis and low fall, result in long-term lying in bed. Either age group leaves a huge burden to the family and the society.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI), a common central nervous system (CNS) trauma, not only causes irreversible neurological dysfunction but also imposes a substantial burden on patients and their surroundings [1]. Despite extensive research and trials of various treatment strategies over the years, the remedy of paralysis after SCI remains elusive [2, 3].…”
Section: Introductionmentioning
confidence: 99%